Total Phenolic Contents and Free Radical Scavenging Activity of Different Parts of Jatropha Species - Akhtar, P.; Yaakob, Z.; Ahmed, Y.; Shahinuzzaman, M.; Ziaul Hyder, M.K. Mohammad (Asian Journal of Chemistry, 2017)
Jatropha species is a worldwide important crop. Each part of this species is used in traditional medicine to treat the various diseases. In this research, antioxidant activity and total phenolic content of different parts of Jatropha species were investigated by using two extraction processes: ultrasound-assisted extraction and maceration. Based on the antioxidant activity and phenolic content, it can be summarized that the extracts obtained by ultrasound-assisted extraction process showed potent antioxidant activity and may be related to their phenolic content. The root extracts of J. gossypiifolia obtained by ultrasound-assisted extraction process showed the highest antioxidant activity and leaves of J. curcas showed highest phenolic contents as compared to maceration process. Among the different parts of these species, all the parts of J. gossypiifolia showed the higher activity as compared to J. curcas. Finally, Jatropha species’ by-products with strong radical scavengers can be considered as potential sources of natural antioxidants.